Moral Education in Volunteering Activities of Young Citizens - Adha, Muhammad Mona; Ulpa, Eska Prawisudawati; Johnstone, Jack McGregor; Cook, Billy L. (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
Moral education through voluntary work or volunteering greatly supports the development of individuals and society specifically in the improvement of social and practical skills, knowledge and experience. Voluntary activity not only forms common good but also develops a caring attitude to act and has a strong interest in working together to make a better community in the aspects of community's role and responsibility. Qualitative research with an ethnographic approach was carried out during the 2018’s Krakatau Festival cultural event which involved 60 volunteers. Observations, interviews, and documentation studies are important parts of data collection and data analysis significantly. This study found that the pattern of responsible activities and implementation of voluntary work can strengthen volunteering awareness and always foster a pattern of good cooperation with fellow volunteers and other work units as a moral responsibility and moral education that is very beneficial for volunteers in the future. The next researcher can conduct research on good volunteering planning preparation and effective and efficient cooperation patterns. Keywords: cooperation; moral education; caring attitude; volunteering; young citizen Pendidikan moral melalui kerja sukarela atau ‘volunteering’ sangat mendukung perkembang-an individu dan masyarakat khusus di dalam meningkatnya keterampilan sosial dan praktis, pengetahuan dan pengalaman. Kegiatan kesukarelaan tidak hanya membentuk kebaikan bagi masyarakat (common good) melainkan juga mengembangkan sikap kepedulian untuk bertindak dan memiliki semangat yang kuat dalam bekerja sama untuk membuat lingkungan masyarakat lebih baik dari aspek peran masyarakat dan tanggung jawab. Penelitian kualitatif dengan pendekatan etnografis dilakukan selama acara budaya Festival Krakatau 2018 dengan melibatkan 60 relawan. Observasi, wawancara, dan studi dokumentasi menjadi bagian penting untuk pengumpulan data dan analisis data secara signifikan. Penelitian ini menemukan bahwa pola aktivitas dan implementasi pekerjaan kesukarelaan yang dilakukan dengan penuh tanggung jawab dapat memperkuat sikap kepedulian relawan dan selalu membina pola kerjasama yang baik dengan sesama relawan dan unit kerja lain sebagai tanggung jawab moral dan pendidikan moral yang sangat bermanfaat bagi diri relawan di masa depan. Peneliti selanjutnya dapat melakukan penelitian mengenai persiapan perencanaan kerja sukarela yang baik dan pola kerjasama yang efektif dan efesien. Kata kunci: kerjasama; pendidikan moral; sikap kepedulian; kesukarelaan; warga negara muda